The Role and Collaboration Between Guidance and Counselling Teachers with Biology Subject Teachers in Overcoming Learning Problems and Difficulties - Khadijah, Khairiyah; Arlizon, Raja; Oktary, Dian; Donal, Donal; Maharani, Azzahra; Naila Anthony, Gena; Sawitri, Isma; Andrina, Mustika; Sundana, Afrizan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research looks at the extent to which collaboration or collaboration is carried out between guidance and counseling teachers and biology subject teachers in optimizing students' potential, making students independent in solving the problems they have. The purpose of this research is to see how collaboration between guidance and counseling teachers and biology teachers functions as a way to deal with problems and learning difficulties faced by students in. In this research, a qualitative approach was used, and data collection methods were used through observation and interviews. The research results show that the role of student subject teachers is very important in finding, understanding, and overcoming learning problems faced by students due to the closeness and intensity of interactions that occur between subject teachers and these students. Furthermore, the research findings show four collaborative steps carried out by subject teachers with guidance and counseling teachers in overcoming student learning difficulties, including: 1) Involving peer tutors 2) Providing variations in the learning process 3) Providing variations in learning models 4) Providing assignments flexibly . Research also shows that there are obstacles and barriers found by subject teachers and guidance and counseling teachers in collaboration in overcoming learning difficulties, namely difficulty finding students' learning obstacles because students are closed and do not want to talk about their problems.